(untitled) (Journal of Education and Development, 2022)
Integrated education advocates that disabled children have the right to receive education equally in ordinary schools. The concept of integrated education means that all children should receive education together in ordinary educational institutions, regardless of their gender, race and physical conditions, which has become the main trend of the development of special education worldwide. And Finland as a fusion education implementation effect is significant country, the development of integration education began in the field of general education comprehensive school reform, since the 1950s, Finland created for special children service institutions, in the 1990s, with the development of integration education, the Finnish government gradually realize the importance of integration education for special children, so the Finnish government put forward the new model of early integration education, namely the special education model, this model can promote the real integration of children in daily education and teaching activities. After that, Finland has taken positive measures to strengthen the number of teachers in integrated education, improve relevant policies and regulations, and develop advanced education models, which are worth learning from and learning from all countries.